Starting solution for some oscillatory rotating flows of magnetohydrodynamic second-grade fluid through porous space - Khan, M.; Safdar, Tanzeela; Azram, Mohammad (Begell House, Inc., 2011)
This paper presents a starting solution for some oscillating flows of an incompressible and electrically conducting second-grade fluid through porous space in a rotating frame of reference. Modified Darcy’s law for a second-grade fluid has been utilized to discuss the flows through porous space. Exact analytical expressions for the velocity field are obtained in the presence of a transverse uniform magnetic field and Hall current using the Fourier sine transforms. The results are presented as a sum of steady-state and transient solutions. In the limiting case when α1 goes to zero, our solutions reduce to those for a Newtonian fluid. The obtained results are sketched for the variations of pertinent parameters and are analyzed through several graphs.